The relationship between social media participation on employees' job performance at Universiti Teknologi Mara Cawangan Terengganu Kampus Kuala Terengganu (UiTMT) / Nor Liyana Mohd Yani - Mohd Yani, Nor Liyana (Faculty of Business and Management, 2018)
This study is about to identify the relationship between social media participation on employees' job performance at Universiti Teknologi Mara Cawangan Terengganu Kampus Kuala Terengganu. The main objective of the study is to identify the impact of social media participations on employees' job performance, to identify the most influencing factors of social media participations on employees' job performance and to determine the relationship between social media participations on employees' job performance. This study only conducted at Universiti Teknologi Mara Cawangan Terengganu Kampus Kuala Terengganu (UiTMT) and the respondents were chosen from non-academic department in the organization. In this study, the questionnaire was used to collect the data by using simple random sampling. The reliability and validity test also had been tested before distributed the questionnaire to respondents. The findings for this study also had been shown in every section by run the data on SPSS Statistics version 23. After get the findings, the researcher will make conclusion and recommendations to improve this study for employee, employer and future research.